2008
DOI: 10.7326/0003-4819-148-8-200804150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Testosterone Metered-Dose Transdermal Spray for Treating Decreased Sexual Satisfaction in Premenopausal Women

Abstract: A daily 90-microL dose of transdermal testosterone improves self-reported sexual satisfaction for premenopausal women with reduced libido and low serum-free testosterone levels by a mean of 0.8 SSE per month. The rate of SSEs with higher and lower testosterone doses did not differ from that with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 21 publications
3
82
0
4
Order By: Relevance
“…The findings of the present study are consistent with other studies that have shown that the side-effect profile of the testosterone patch appears to be acceptable to women receiving estrogen treatment and those who have undergone natural menopause and are taking estrogens with a progestin, as well as those being treated with testosterone alone (17,19,20,22). Although the evidence of the potential benefit of testosterone treatment in women suffering from HSDD is very convincing, there has been a lack of such data for treatment options in transsexual women.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of the present study are consistent with other studies that have shown that the side-effect profile of the testosterone patch appears to be acceptable to women receiving estrogen treatment and those who have undergone natural menopause and are taking estrogens with a progestin, as well as those being treated with testosterone alone (17,19,20,22). Although the evidence of the potential benefit of testosterone treatment in women suffering from HSDD is very convincing, there has been a lack of such data for treatment options in transsexual women.…”
Section: Discussionsupporting
confidence: 82%
“…77 Another showed marginal benefit from one of three doses of transdermal testosterone in premenopausal women with early morning serum free testosterone of less than or equal to 1.1 pg/ml. 78 The highest of the three doses, aimed to raise free testosterone levels to at least the 75th percentile failed to show benefit beyond placebo as did the smallest (one-third) dose. The one-half dosage allowed 0.7 more sexually satisfactory events per month than placebo, but outcome as measured by the Sabbatsberg Sexual Self-rating Scale was similar to placebo.…”
Section: Systemic Estrogenmentioning
confidence: 99%
“…Adding oestrogen or testosterone treatment to the antipsychotic medication may assist these sexual dysfunction problems in postmenopausal and premenopausal women (Davis et al, 2008), but the possible risks of these treatments must be considered. High prolactin levels can also cause anovulatory menstrual cycles and hence infertility.…”
Section: Development Of Schizophrenia In Womenmentioning
confidence: 99%